Lecturers’ Speech Acts in Arabic Language Learning Interactions at UIN Sulthan Thaha Saifuddin Jambi - Prihartini, Yogia; Buska, Wahyudi (AT-TA'LIM, 2020)
This study aims to describe the type and function of lecturers’ speech acts in the interaction of learning Arabic at UIN Sulthan Thaha Saifuddin Jambi. Where in the classroom, the lecturers had important roles in the teaching and learning process. They always use speech as medium to convey ideas to students. Lecturers are also expected to function as active communicators in Arabic lectures. The interaction that is built by lecturers and students is inseparable from the speech act. A qualitative approach was implemented where the data taken from lecturer utterances in Arabic learning interactions were obtained from Arabic lecturers. Data collection was taken by using non-participant observation technique. Mechanical devices and stationery are positioned as data collection aids. Data analysis includes data reduction, data presentation, and data collection/verification results. The finding showed that the lecturers use five types of speech acts in Arabic learning interactions, namely directive, assertive, co missive, expressive, and declarative acts. The finding also showed that there are social and educational functions used by Arabic lecturers. Social functions consist of four categories, namely, competitive functions, convivial functions, collaborative functions, and conflictive functions. While, the educational function of lecturer speech acts consists of nine types, namely, giving a positive impression of the material, directing focus, inclusive learning situations, exclusive learning situations, expressing specific things, encouraging students to build conclusion, controlling the learning situation, and providing motivation to students. The results indicated that the lecturers' speech acts deal with social problems and learning objectives.